RABBIT MANGE INFESTATION AND ITS THERAPEUTIC MANAGEMENT - P. Gopu; T. Chandrasekar; M. Arul Prakash; Karu. Pasupathi; D. Balasubramaniam (Indian Journal of Veterinary and Animal Sciences Research, 2025)
A study was conducted on Soviet chinchilla rabbits (n=28) with mange infestation at Rabbit Breeding Unit, Post Graduate Research Institute in Animal Sciences, Kattupakkam, Tamil Nadu. The infested rabbits evinced the symptoms of alopecia, anorexia, pruritus, skin erosion, and dry crust like lesions on extremities, ears, nose, and face. The affected rabbits were grouped into four groups (7 for each group) for different therapeutic treatments along with antihistamine and vitamin supplementation for a period of 4 weeks with weekly intervals. It was established that treatment group 4 was successful in curative and early revival of mange infestation.